Immunohistochemical, histological and ultrastructural evaluation of the effects of leptin on testes in mice - Kus, I; Sarsilmaz, M; Canpolat, S; Yilmaz, B; Kelestimur, H; Akpolat, N; Ozogul, C (Taylor & Francis Inc, 2005)
This study was undertaken to examine the effects of leptin on testes in mice. For this purpose, 12 male mice were divided into two groups. Animals in Group I were designated as control. Mice in Group 11 were injected daily with leptin for 5 days. All animals were decapitated at the end of the experiment. The testes were removed and weighed out. Testicular tissue specimens were processed for light and electron microscopic examination and semi-quantitative evaluation of immunohistochemical testosterone staining. Intensity of immunostaining was determined on a scale between 0 (no staining) and 5 (heavy staining). For morphometric comparison, diameters Of seminiferous tubules from each group were measured. In the leptin injected group, testicular weights and diameters of seminiferous tubules were significantly increased in comparison to control values. In light microscopic examination, an increase in secretory granules in the cytoplasm of Leydig cells was observed after leptin treatment. In the same group, distinct changes indicative of increased cell activation were seen in the ultrastructure of Leydig cells. Amount of mitochondria, lysosomes and cytoplasmic secretory granules were increased. Furthermore, an increase in extensiveness of rough endoplasmic reticulum was noted in this group. Immunohistochemical testosterone staining of the cytoplasm of Leydig cells was heavy (5+) in the leptin treated mice compared to mild score (2+) in the control mice. Additionally, heavy immunostaining of testosterone was also observed in the interstitial space after injection of leptin. The present findings indicate that testicular functions and synthesis of testosterone increase after administration of leptin.
Keywords: immunohistochemistry; leptin; light and electron microscopy; testis